Constitutional Disobedience oleh Pembentuk Undang-Undang dan Penegakan Judicial Order - Triyadi, Wahyu Indra (JOURNAL of LEGAL RESEARCH, 2025)
The Constitutional Court has the authority embedded by the constitution regarding the examination of laws against the Constitution of the Republic of Indonesia (UUD NRI) 1945 whose decisions are final and binding. The authority aims to ensure that a norm in the law remains in compliance with the values in the constitution. Therefore, it is appropriate for the law-making body as the addresat of the Constitutional Court's decision to follow up on the decision in the legislative process. However, in practice, there is often non-compliance by law making institutions with the Constitutional Court Decision. The non-compliance with the Constitutional Court's Decision is rooted in the legislative process by the lawmaking body that contradicts the contents of the decision. This paper aims to analyse the idea of judicial order enforcement in realising the compliance of law making institutions in following up the Constitutional Court Decision. This research uses a normative juridical research method through a conceptual approach to identify these problems. The results of this study conclude that, first, there are several factors that cause the non-compliance of the legislative body with the Constitutional Court Decision and the absence of sanctions against the legislative body that does not comply with the Constitutional Court Decision. Secondly, it discusses the legal implications of the non-compliance of law making institutions with the Constitutional Court Decision. Third, offering a judicial order solution to the Constitutional Court Decision by affirming expressis verbis the clause to include the Constitutional Court Decision, which is a source of law in the lawmaking process.